Production of biochar from rice straw and its application for wastewater remediation − An overview - Foong, Shin Ying; Chan, Yi Herng; Chin, Bridgid; Lock, Serene Sow Mun; Yee, Cia Yin; Yiin, Chung Loong; Peng, Wanxi; Lam, Su Shiung (Elsevier, 2022)
The valorization of biochar as a green and low-cost adsorbent provides a sustainable alternative to commercial wastewater treatment technologies that are usually chemical intensive and expensive. This review presents an in-depth analysis focusing on the rice straw-derived biochar (RSB) for removal of various types of contaminants in wastewater remediation. Pyrolysis is to date the most established technology to produce biochar. Subsequently, biochar is upgraded via physical, chemical or hybrid activation/modification techniques to enhance its adsorption capacity and robustness. Thus far, acid-modified RSB is able to remove metal ions and organic compounds, while magnetic biochar and electrochemical deposition have emerged as potential biochar modification techniques. Besides, temperature and pH are the two main parameters that affect the efficiency of contaminants removal by RSB. Lastly, the limitations of RSB in wastewater remediation are elucidated based on the current advancements of the field, and future research directions are proposed.